PENGARUH BERBAGAI JENIS KOMPOS TERHADAP PERTUMBUHAN BIBIT SUKUN (Artocarpus communis Forst) DI DAERAH TANGKAPAN AIR DANAU TOBA KECAMATAN HARANGGAOL HORISON - Suryanto B Sinaga; Budi Utomo; Afifuddin Dalimunthe (Peronema Forestry Science Journal, 2015)
The Catchment Area of Lake Toba experienced considerable environmental damage at this time. Lake Toba community activities that transform forests into agricultural land requiring rehabilitation efforts so that the condition of soil fertility can be restored. One of the efforts is to plant breadfruit because breadfruit has high adaptability, fast growing, does not have a requirement to grow a lot and suitable to grow in the highlands. This study aimed to observed the response of seedling growth breadfruit (Artocarpus communis Forst) for the provision of additional materials to the growing media water-retaining compost. Type of compost that was used there are 4 types of Bernas, Bokashi, Rice Husk, Municipal Solid Waste. This study was conducted in September-November 2014. The study was conducted at Catchment Area of Lake Toba, District Haranggaol, Simalungun. The results showed that the use of different types of compost did not significantly affect the average height increment, diameter, leaf area, crown area, number of leaves and water content. Keywords: Breadfruit, Compost, Bernas, Bokashi, Catchment Area of Lake Toba